Notes by Jan Górnicki (Ber Oszer Weisbaum) - Engelking, Barbara (Zagłada Żydów. Studia i Materiały, 2013)
Jan Górnicki’s notes, written in May 1945, concern the days of the great deportation action in the Warsaw ghetto in July 1042. He was a young boy then, living with his mother and trying to earn some money riding a rickshaw. He describes the deteriorating conditions of the life in the ghetto and people in quest of any means to survive. In the end he presents dramatic scenes from Umschlagplatz, where the ghetto inhabitants were gathered for deportation.